A importância da arte como meio de reciclagem e como formação de um novo pensamento ambiental - Palhaci, Maria do Carmo Jampaulo Plácido [UNESP]; Palhaci, Talitha Plácido [UNESP]; Hellmeister, Luis Antonio Vasques [UNESP]; Nicola, Ricardo Luís [UNESP] (My University, 2012)
The question related to recyclable material has been pointed by environmental researchers as one of the most serious urban problems today. Therefore, the importance of disclosure and clarification related to recycling techniques is highlighted, as well as a critical and extensive reflection related to the cultural values of society about current economic rationality that prioritizes a unlimited consumerism. We conducted a survey in the city of Bauru and asked how often people separated recyclable materials for selective collection. We found that 18% of these people have never performed this type of activity. Thus we emphasize the importance of art in creating alternative ways of dealing with the recyclable material, that involves social, economic and cultural needs of a population; contributing to preserve the environment such as the creation of a new rationality.
Keywords: Recycling; Art; Environment